Mapping quantitative trait loci for fusarium root rot in common bean (phaseolus vulgaris l.) - Kamfwa, K.; Okori, Patrick; Mwala, M; Mukankusi, Clare Mugisha (Pan-Africa Bean Research Alliance, 2016)
The common bean is a primary protein source in the diet of many low-income populations. Bean root rots occur in most bean fields. Genetic resistance to Fusarium root rot caused by Fusarium solani f.sp. phaseoli is polygenic and is strongly influenced by environmental factors that confound the expression and detection of resistance mechanisms. Response to selection for root rot resistance is slow due to genetic complexity of the trait that makes it difficult to evaluate. Indirect selection for Fusarium root rot resistance based on DNA markers linked to the resistance QTL would facilitate improvement of Fusarium root rot, given the limitations of field selection. The study is aimed at identify significant QTL- simple sequence repeat (SSR) marker associations, which could be used to facilitate marker-assisted selection for Fusarium root rot resistance in common bean.